(untitled) (Global Journal of Management and Business Research, 2014)
Under intense and rapid change of marketplace, researchers have been studying the key factor for firms and organizations to survive in the market. Customer loyalty has been a key factor and a recently researched topic in maintaining the competitiveness of the organizations. This article is going to discuss about customer loyalty in relationship marketing and internet marketing. It also aims to discuss the better marketing strategy that can contribute in gaining higher level of customer loyalty. The methods of communication for both relationship marketing and internet marketing are also explained to identify which marketing strategy could achieve higher level of customer loyalty.